Host autophagy limits Toxoplasma gondii proliferation in the absence of IFN-γ by affecting the hijack of Rab11A-positive vesicles - Pan, Lingtao; Yang, Yimin; Chen, Xueqiu; Zhao, Mingxiu; Yao, Chaoqun; Sheng, Kaiyin; Yang, Yi; Ma, Guangxu; Du, Aifang (Frontiers in Microbiology, 2022)
Autophagy has been recognized as a bona fide immunological process. Evidence has shown that this process in IFN-γ stimulated cells controls Toxoplasma gondii proliferation or eliminates its infection. However, little is known about the effect of T. gondii infection on the host cell autophagy in absence of IFN-γ. Here, we report increased LC3 II, autophagosome-like membrane structures, enhanced autophagic flux, and decreased lysosomes in a range of mammalian cell lines without IFN-γ treatment after T. gondii infection. Specifically, disruption of host atg5 (a necessary gene for autophagy) in HeLa cells promoted the intracellular replication of T. gondii, with the transcript level of rab11a increased, compared with that in wild-type cells. Further, after T. gondii infection, the abundance of Rab11A remained stable in wild-type HeLa cells but decreased in atg5−/− mutant. Disruption of rab11a in the HeLa cells compromised the proliferation of T. gondii and increased the transcription of gra2 in the parasite. Compared to the T. gondii wild-type RH∆ku80 strain, the ∆gra2 mutant induces enhanced host autophagy in HeLa cells, and results in slower replication of the parasite. Collectively, these results indicate that host cell autophagy can limit T. gondii proliferation in an IFN-γ independent manner, possibly by affecting the hijack of host Rab11A-positive vesicles by the parasite which involved TgGRA2. The findings provide novel insights into T. gondii infection in host cells and toxoplasmosis research.